TMOD-17. A NOVEL ADENOVIRAL-PERMISSIVE, IMMUNOCOMPETENT HAMSTER MODEL TO EVALUATE ONCOLYTIC ADENOVIRAL THERAPY FOR GLIOBLASTOMA. (5th November 2018) - Phillips, Lynette; Li, Shoudong; Gumin, Joy; Ledbetter, Daniel; Hossain, Anwar; Kerrigan, Brittany; Gomez-Manzano, Candelaria; Fueyo, Juan; Lang, Frederick
Abstract: Treatment with the oncolytic adenovirus, Delta-24-RGD, resulted in dramatic tumor response in 20% of recurrent malignant glioma patients in a recent Phase I clinical trial. Studies in immunocompetent mice corroborate the patient data indicating that Delta-24-RGD effects are due to both direct tumor cell lysis and viral-mediated anti-tumor immune response. However, it is unclear why only a fraction of patients responds in this manner. Due to poor adenoviral replication in immunocompetent mouse models, the mechanisms by which Delta-24-RGD elicits an effective anti-tumor immune response remain poorly understood. Therefore, we sought to develop a syngeneic Syrian hamster glioma model that is both adenovirus replication-permissive and immunocompetent. We transformed hamster neural stem cells with hTERT, simian virus 40 large T antigen, and h-RasV12 and re-implanted the transformed cells into hamster brains where they developed into tumors. Hamster glioma stem cells (GSCs) were isolated from the resulting tumors and were re-implanted into naive hamster brains using a guide-screw system. In vitro, hamster GSCs supported viral replication and were susceptible to Delta-24-RGD mediated cell death. In vivo, hamster GSCs consistently developed into highly proliferative tumors resembling high-grade glioma. Following delivery of Delta-24-RGD by intratumoral injection, immunohistochemistry for viral proteins demonstrated viral infectivity and replication in hamster gliomas. Flow cytometric analysis of hamster gliomas revealed increased T-cell infiltration in Delta-24-RGD infected tumors. Delta-24-RGD treatment of tumor-bearing hamsters led to significantly increased survival compared to hamsters treated with PBS. In summary, we have developed an adenovirus-permissive, immunocompetent hamster glioma model that provides a novel platform in which to study the interactions between tumor cells, the host immune system, and oncolytic adenoviral therapy.